Sustainable development and quality assurance in higher education : transformation of learning and society - Fadeeva, Zinaida; Galkute, Laima; Mader, Clemens; Scott, Geoff (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2014)
"Higher education has a central role in helping our world address its interlaced social, cultural, economic and environmental challenges. Our universities and colleges can do this by identifying and testing solutions in collaboration with the regions they serve, and by building the leaders of tomorrow. But to do this higher education institutions (HEIs) must transform themselves, and this involves bringing together best practice in quality management and improvement for tertiary education with best practice in education for sustainable development. This book seeks to provide those interested in addressing this double helix of transformation with tested strategies and pathways for undertaking the journey successfully. It pays particular attention to dynamic interplays between organizational, national and international development in higher education policies and practices relevant for quality assurance. It also explores changing understandings of the notion of quality in higher education, relations of quality systems and other HEI strategies and questions of learner competences in the context of HEI strategies. "--
Machine generated contents note: -- 1. Assessment for Transformation: Higher Education Thrives in Redefining Quality Systems; Zinaida Fadeeva, Laima Galkute, Clemens Mader and Geoff Scott 2. Rankings and the Reconstruction of Knowledge during the Age of Austerity; Ellen Hazelkorn 3. Sustainable Engagement: Towards a Participative Quality Culture of Sustainable Development in Higher Education; Oliver Vettori and Christian Rammel 4. The Role of Assessment and Quality Management in Transformations towards Sustainable Development: The Nexus between Higher Education, Society and Policy; Clemens Mader 5. Drivers for Change in the Austrian University Sector: Implications for Quality Management; Andrea Bernhard and Nadine Shovakar 6. Quality Assurance System based on Sustainable Development Paradigm: The Lithuanian Perspective; Laima Galkute 7. Quality System Development at the University of Graz: Lessons Learned from the Case of RCE Graz-Styria; Friedrich M. Zimmermann, Andreas Raggautz, Kathrin Maier, Thomas Drage, Marlene Mader, Mario Diethart and Jonas Meyer 8. STARS as a Multi-Purpose Tool for Advancing Campus Sustainability in the USA; Monika Urbanski and Paul Rowland 9. Sustainability and Values Assessment in Higher Education; Arthur Lyon Dahl 10. Educating Sustainability Change Agents by Design: Appraisals of the Transformative Role of Higher Education; Katja Brundiers, Emma Savage, Steven Mannell, Daniel J. Lang and Arnim Wiek 11. Quality Management of Education for Sustainability in Higher Education; Geoff Scott 12. Implementing Education for Sustainable Development (ESD) Concept in Higher Education Institutions: Case Study of Albukhary International University AIU), Malaysia; Salfarina Abdul Gapor, Zainal Abidin Sanusi, Dzulkifli Abdul Razak and Abd Malik Abd Aziz.
IQAC
Trim Education
Keywords: Sustainable development -- Study and teaching (Higher); Education, Higher -- Administration; Education, Higher -- Social aspects; Quality assurance; BUSINESS & ECONOMICS / Quality Control; EDUCATION / Higher; EDUCATION / Educational Policy & Reform / General; EDUCATION / Organizations & Institutions